LITERATUR REVIEW: PENGARUH RATING TOKO DAN JUMLAH PENGIKUT TERHADAP KEPERCAYAAN KONSUMEN PADA MARKETPLACE - Desferando Desferando; Desi Ratnasari; Irvan Rolyesh Situmorang (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the rapidly evolving digital economy ecosystem of Indonesia, consumer behavior in marketplace transactions has undergone a significant paradigm shift from physical assessment to digital reputation-based evaluation. This literature review article aims to conduct an in-depth and comprehensive analysis of how store rating and number of followers function as crucial instruments in shaping consumer trust that ultimately leads to purchasing decisions. Using a library research method exploring ten national scientific journals from 2021 to 2025, this study synthesizes various relevant empirical findings. The literature review consistently shows that store ratings are a highly reliable predictor of service quality, while the number of followers serves as an indicator of popularity and social validation. Both elements, partially and simultaneously, have a positive and significant influence in mitigating risk perception and building strong consumer trust, which ultimately determines the success of purchasing decisions on increasingly competitive e-commerce platforms.